Social Network Between Farmers And Vegetable Traders In Tulehu Market - Sabda Z Denovan Tawainella (International Journal of Economics, Business and Innovation Research, 2024)
This research was carried out in Tulehu, Salahutu District, Central Maluku Regency. The problems studied are 1. How is cooperation built in the social network of vegetable farmers and traders at the Tulehu market, Salahutu subdistrict, Central Maluku Regency? 2. To find out what type of social network is the vegetable farmers in Hanyie - Suli Village and traders in the Tulehu market, Salahutu sub-district, Central Maluku Regency? The aim of the research is to find out 1. How cooperation is built in the social network of vegetable farmers and traders at the Tulehu market, Salahutu sub-district, Central Maluku Regency. 2. Know the types of social networks of vegetable farmers and traders in the Tulehu market, Salahutu sub-district, Central Maluku Regency. The sample used in this research was the Simple Purposive Sampling technique. In this research, there were 4 vegetable farmers and 5 vegetable traders. Researchers use the theory of Types of Social Networks, a theory that explains three types of social networks where there must be an interest network, a sentiment network and a power network. As a result of the general research carried out, the author can say that there are three types of networks in the Tulehu market, namely a network with a type of social network of farmers and traders bridged by social capital and marketing. The author uses the descriptive qualitative method.